Exp-function method for the exact solutions of fifth order KdV equation and modified Burgers equation - Inan, Ibrahim E.; Ugurlu, Yavuz (Elsevier Science Inc, 2010)
In this paper, we implemented the exp-function method for the exact solutions of the fifth order KdV equation and modified Burgers equation. By using this scheme, we found some exact solutions of the above-mentioned equations. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Fifth order KdV equation; Modified Burgers equation; Exp-function method; Exact solutions